Negotiating Customary Justice and Social Reconciliation: The Role of Peumat Jaroe in Acehnese Dispute Resolution - Erha Saufan Hadana; Islahul Umam; Iswadi Iswadi; Amzar Ardianyah; Rizkal Rizkal (Yayasan Abdurrauf Cendekia Nusantara, 2026)
Dispute resolution in Acehnese society exhibits distinctive characteristics through the role of customary institutions at the gampong level. Communities often prefer customary mechanisms to formal judicial processes because they are considered more compatible with local values, cultural norms, and communal interests. The contrast between the legalistic orientation of the formal justice system and the relationship-restoring nature of customary law raises important questions regarding the normative foundations, principles, and cultural meanings of customary dispute resolution. This study therefore examines: (i) the normative bases and authority of customary institutions in Aceh’s dispute resolution system; (ii) the customary principles applied in resolving disputes at the gampong level; and (iii) the juridical and cultural significance of the peumat jaroe ritual as a symbol of reconciliation. This research employs a normative legal approach within the framework of legal anthropology, focusing on the interaction between legal norms, cultural values, and social practices. The findings reveal that customary institutions in Aceh derive dual legitimacy from both legal recognition and public trust. Their dispute resolution mechanisms are guided by the principles of deliberation (musyawarah), consensus (mufakat), kinship, and restorative justice, all of which contribute to sustainable peace. The peumat jaroe ritual serves as a symbolic affirmation of reconciliation and the restoration of social harmony. Accordingly, Acehnese customary dispute resolution demonstrates a harmonious integration of law, culture, and social order in maintaining community cohesion and peace. [Penyelesaian sengketa dalam masyarakat Aceh menunjukkan karakteristik yang khas melalui peran lembaga adat di tingkat gampong. Dalam praktiknya masyarakat cenderung lebih memilih mekanisme adat dibandingkan peradilan formal karena dinilai lebih sesuai dengan nilai sosial, budaya, dan kebutuhan komunitas. Perbedaan orientasi antara sistem hukum formal yang bersifat legalistik dan hukum adat yang menekankan pemulihan hubungan sosial menimbulkan pertanyaan mengenai dasar normatif, prinsip, serta makna kultural dalam praktik penyelesaian sengketa tersebut. Rumusan masalah dalam penelitian ini meliputi: bagaimana landasan normatif dan kewenangan lembaga adat dalam sistem penyelesaian sengketa di Aceh, bagaimana prinsip-prinsip adat yang diterapkan dalam penyelesaian sengketa di tingkat gampong, serta bagaimana makna ritual peumat jaroe sebagai simbol rekonsiliasi dalam keadilan adat Aceh. Penelitian ini menggunakan pendekatan normatif dengan perspektif antropologi hukum, yang mengkaji hubungan antara norma hukum, nilai budaya, dan praktik sosial dalam masyarakat. Hasil penelitian menunjukkan bahwa keberadaan lembaga adat di Aceh memiliki legitimasi ganda, yaitu secara yuridis melalui pengakuan konstitusional dan regulasi khusus, serta secara sosial melalui kepercayaan masyarakat. Prinsip-prinsip penyelesaian sengketa adat seperti musyawarah, mufakat, kekeluargaan, dan keadilan restoratif menjadi dasar dalam mencapai perdamaian yang berkelanjutan. Selain itu, ritual peumat jaroe memiliki makna simbolik yang penting sebagai penanda berakhirnya konflik dan pemulihan hubungan sosial di hadapan masyarakat. Dengan demikian, sistem penyelesaian sengketa adat di Aceh mencerminkan integrasi antara hukum, budaya, dan nilai sosial yang berorientasi pada terciptanya harmoni dalam kehidupan masyarakat.]